Application of Cloud Model in Evaluation of Urban Vulnerability to Floods Based on Improved Game Theory and Combined Weight - WANG Dayang (Renmin Zhujiang)
The urban vulnerability to floods reflects the state of destruction and damage of human,society and economic properties in the city by floods.Taking 14 cities of Guangxi Zhuang Autonomous Region as examples,this paper introduces the cloud model theory method into the evaluation of urban vulnerability to floods,establishes an evaluation factor system for flood vulnerability with five vulnerability levels,improves the game theory to ensure the positive value of combination coefficient based on the subjective and objective weights,and then determines the cooperative weights.The research shows that the cloud model can cope with the uncertainty in the evaluation studies well by taking into account the ambiguity and randomness of factors.In overall,cities in the middle and east Guangxi have higher vulnerability level,followed by those in the west and north Guangxi,and then those in the south Guangxi.